Carbon Dots Promote the Performance of Anodized Nickel Passivation Film on Ethanol Oxidation by Enhancing Oxidation of the Intermediate†. Issue 5 (13th April 2021) - Shi, Yandi; Liao, Fan; Zhu, Wenxiang; Shi, Huixian; Yin, Kui; Shao, Mingwang
Main observation and conclusion: Ethanol is considered a better fuel than methanol in direct alcohol fuel cells because of the high energy density and low toxicity. Compared with noble metal catalysts, nickel‐based catalysts are much cheaper in price. However, present nickel‐based catalysts still surfer from some disadvantages such as low activity and high overpotential. In this paper, we show a new and high efficient nickel‐ based catalyst for ethanol oxidation. A layer of anodized nickel passivation film (Ni‐APF) was formed on the surface of nickel sheet by anodic oxidation method with carbon dots (CDs) as co‐catalyst. At the current density of 110 mA·cm −2, the potential for Ni‐APF/CDs was only 0.541 V ( vs . Ag/AgCl), which was 18.8% lower than that of Ni‐APF. Low overpotential could reduce electrode thermal loss and increase output energy. Ni‐APF/CDs showed 144.4 mA∙cm −2 peak current density at peak potential 0.662 V ( vs . Ag/AgCl), which was 31% higher than that of Ni‐APF (110.3 mA∙cm −2 ). In this system, CDs mainly function in the increase of charge‐transfer capacity and the promotion oxidation of carbonaceous intermediates. Abstract : A layer of dense anodized nickel passivation film (Ni‐APF) was formed on the surface of nickel sheet by anodic oxidation method, with carbon dots (CDs) as co‐catalyst. Ni‐APF/CDs showed 144.4 mA∙cm −2 peak current density at peak potential 0.662 V ( vs . Ag/AgCl), which was 31% higher than that of Ni‐APF (110.3 mA∙cm −2 ). In this system, CDs mainly function in the increase of charge‐transfer capacity and the promotion oxidation of carbonaceous intermediates.